2021
DOI: 10.3126/ajms.v12i3.32606
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cardiac function in COPD patients and correlation with disease severity: A cross sectional study

Abstract: Background: Chronic obstructive pulmonary disease (COPD) has considerable effects on cardiac functions, including those of the right ventricle, left ventricle, and pulmonary blood vessels. Most of the increased mortality associated with COPD is due to cardiac involvement. Echocardiography provides a rapid, non-invasive portable, and almost accurate method to evaluate the right ventricle function, right ventricular filling pressure, tricuspid regurgitation, left ventricular function, and valvular functions. Ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A decrease in the value of TAPSE was found to be 4.2% in GOLD II, 10.3% in GOLD III, and 37.9% in GOLD IV. 4 Tannus-Silva, et al also found that 16% of 50 stable COPD patients with a mean of FEV1 value of 37.6% (± 19.3) pred had RV dysfunction using TAPSE values. 8 It is undeniable that COPD can cause heart failure, especially in the right heart.…”
Section: Prevalence Of Heart Failurementioning
confidence: 91%
See 2 more Smart Citations
“…A decrease in the value of TAPSE was found to be 4.2% in GOLD II, 10.3% in GOLD III, and 37.9% in GOLD IV. 4 Tannus-Silva, et al also found that 16% of 50 stable COPD patients with a mean of FEV1 value of 37.6% (± 19.3) pred had RV dysfunction using TAPSE values. 8 It is undeniable that COPD can cause heart failure, especially in the right heart.…”
Section: Prevalence Of Heart Failurementioning
confidence: 91%
“…Basak, et al also found a 16% prevalence of decreased RV systolic function with a distribution of 4.2% in 24 GOLD II subjects, 10.3% in 39 GOLD III subjects, and 37.9% in 29 GOLD IV subjects. 4 Tannus-Silva, et al also found 8 subjects (16%) of 50 stable COPD patients with a mean FEV1 value of 37.6% (±19.3) pred who had RV dysfunction using TAPSE values. 8 Gupta, et al found a decrease in LV systolic function of 7.5% in 40 stable COPD patients and Putrawan found a 5.7% prevalence of LV dysfunction in stable COPD subjects.…”
Section: Relationship Between Lung Function and The Dimensions Functi...mentioning
confidence: 92%
See 1 more Smart Citation